2011
DOI: 10.1136/gut.2010.222844
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fatty acid translocase CD36 upregulation is associated with insulin resistance, hyperinsulinaemia and increased steatosis in non-alcoholic steatohepatitis and chronic hepatitis C

Abstract: Hepatic FAT/CD36 upregulation is significantly associated with insulin resistance, hyperinsulinaemia and increased steatosis in patients with NASH and HCV G1 with fatty liver. Translocation of this fatty acid transporter to the plasma membrane of hepatocytes may contribute to liver fat accumulation in patients with NAFLD and HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
241
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(277 citation statements)
references
References 47 publications
22
241
1
4
Order By: Relevance
“…31,37 Recently, it was reported that abnormal upregulation of CD36 on the plasma membrane of hepatocytes contributes to hepatic fat accumulation, insulin resistance, and hyper-insulinemia in patients with NAFLD. 38,39 Consistent with these reports, the hepatic mRNA and protein levels of PPAR-g and CD36 were abnormally elevated, and hyperglycemia and hyperinsulinemia were also observed in HFD-fed mice (Figures 6a-c and Table 3), confirming that the PPAR-g-signaling pathway and CD36 are involved in HFD-induced NAFLD. Our data also clearly showed high levels of CYP2E1 mRNA expression and lipid peroxidation products in the livers of HFD-fed mice (Figures 3a and b).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…31,37 Recently, it was reported that abnormal upregulation of CD36 on the plasma membrane of hepatocytes contributes to hepatic fat accumulation, insulin resistance, and hyper-insulinemia in patients with NAFLD. 38,39 Consistent with these reports, the hepatic mRNA and protein levels of PPAR-g and CD36 were abnormally elevated, and hyperglycemia and hyperinsulinemia were also observed in HFD-fed mice (Figures 6a-c and Table 3), confirming that the PPAR-g-signaling pathway and CD36 are involved in HFD-induced NAFLD. Our data also clearly showed high levels of CYP2E1 mRNA expression and lipid peroxidation products in the livers of HFD-fed mice (Figures 3a and b).…”
Section: Discussionsupporting
confidence: 75%
“…CD36 has also been reported to contribute to insulin resistance and hyper-insulinemia. 38,48 Interestingly, the increased level of plasma insulin in the HFD þ oxLDL group under hyperglycemic condition was significantly lower than that of the HFD-fed group (Table 4). Similar results were also obtained with RD þ oxLDL mice (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In the hyperinsulinaemic, insulin-resistant state, as seen in NAFLD, this tight homeostatic control of lipid and carbohydrate is partially lost. IR is associated with uncontrolled adipose tissue lipolysis as well as increased hepatic expression of fatty acid transporter proteins required for fatty acid uptake into the liver (122). Furthermore, obesity and IR are associated with increased re-esterification of fatty acids (123).…”
Section: Insulinmentioning
confidence: 99%
“…The combination of increased fatty acid release from adipose tissue and decreased clearance by skeletal muscle results in hyperlipidemia and increased reliance on the liver to clear fatty acids (Lewis et al 2002, Jonkers et al 2013, Janssens et al 2015. Hepatic expression of Cd36, a fatty acid transporter, is increased with alcohol or high-fat feeding in mice and in NAFLD (Miquilena-Colina et al 2011, Clugston et al 2014. Hyperinsulinemia alone can stimulate hepatic Cd36 expression, and is suggested as a primary mechanism driving hepatic lipid accumulation (Steneberg et al 2015).…”
Section: Adipose Tissue Lipolysis and Hepatic Lipid Uptakementioning
confidence: 99%